Analysis of The Quality of Loading and Unloading Services To Customer Satisfaction at PT Jakarta International Container Terminal Year (2021) - Siregar, Insan Habibi; Ramadhan, Rafly Hendikesta; Suparman, Asep; Primadi, Andri (Institut Transportasi dan Logistik Trisakti, 2023)
PT Jakarta International Container Terminal (Persero) is a State-Owned Enterprise (BUMN) engaged in port services to uphold the smooth flow of marine vessels. One of the strategies that can uphold success in business is that the company can provide optimal service quality, to be able to win the competition which in the end will get maximum profit. Pt. Jakarta International Container Terminal is a large port, in addition to serving freight transportation, it also serves container loading and unloading.